2015
DOI: 10.1542/peds.2014-1269
|View full text |Cite
|
Sign up to set email alerts
|

A Quality Improvement Project to Reduce Length of Stay for Neonatal Abstinence Syndrome

Abstract: BACKGROUND AND OBJECTIVE: Neonatal abstinence syndrome (NAS), a self-limiting condition, is associated with clinical symptoms that may require pharmacological intervention. Optimal treatment of NAS remains undetermined, but the hospital length of stay (LOS) for patients with NAS is partially dependent upon a standard treatment protocol used. Prolonged LOS for patients with NAS can lead to adverse patient harm, impaired maternal-infant attachment, and significant health care costs. Therefore, we conducted a qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…29 Similarly, other research has concentrated on increasing family involvement in the delivery of nonpharmaceutical therapy and a "care bundle" approach to management. 30,31 These studies assessed intervention efficacy in terms of hospital duration and/or health care costs, and all demonstrated an improvement. It could be argued, therefore, that a model including family focused care which collaboratively fosters a therapeutic mother-child relationship and places breastfeeding at its center should also improve clinical and economic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…29 Similarly, other research has concentrated on increasing family involvement in the delivery of nonpharmaceutical therapy and a "care bundle" approach to management. 30,31 These studies assessed intervention efficacy in terms of hospital duration and/or health care costs, and all demonstrated an improvement. It could be argued, therefore, that a model including family focused care which collaboratively fosters a therapeutic mother-child relationship and places breastfeeding at its center should also improve clinical and economic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge may be used to adjust hospital practices to improve families' experiences of the NAS hospitalization. 2,24,25 More research is needed to better understand the complex social and emotional aspects of NAS to further improve family-centered NAS care, both in the hospital and in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent multicenter Ohio collaborative reports and a single-center study in NICUs showed a decreased LOS to between 18 and 23 days with use of a standardized weaning protocol. 8,26,27 Recent US national data show average LOS for a pharmacologically treated infant is 23 days. 3 Limitations include that the project occurred in a children's hospital within a hospital.…”
Section: Figurementioning
confidence: 99%